Assessing the attraction of narrow-spectrum and broad-spectrum artificial light to nocturnal insects: patterns and predictive models - Hao, Qingli; Liu, Gang; Wang, Lixiong; Xin, Pengyuan; Yu, Juan; Yu, Zejun; Chen, Xiaochao (Frontiers in Ecology and Evolution, 2023)
The significant ecological risks posed by artificial light at night (ALAN) are rapidly increasing globally. The rapid development of narrow-spectrum light-emitting diodes (LEDs) presents various challenges for reducing fatal attraction to ALAN and associated ecological risks. However, the potential risks and variations in the fatal attraction have not been precisely measured and assessed.Insects are ecological indicator species and photosensitive animals that are often fatally attracted to ALAN. In this paper, we conduct phototaxis experiments in Tianjin, China. We explored insect phototactic behavior and rhythms by comparing the effects of different time periods and spectra on the number of phototactic insects using UV light as a baseline. The spectra include seven narrowspectrum lights with different peak wavelengths and two broad-spectrum lights with different color temperatures. In general, shorter wavelength light was more attractive: short-wave blue light (447 nm and 478 nm) was the most attractive, followed by medium-wave green light (500 nm and 519 nm) and long-wave red light (627 nm, 660 nm, and 740 nm). Insects were more attracted to 4,500 K LEDs than 3,000 K LEDs, but the difference in attraction between 4,500 K and 3,000 K LEDs was not significant. For eco-risk periods, that is, the peak hours of the fatal attraction of insects to ALAN in the field, LEDs attract insects at the fastest rate from 20:00 to 21:30 (from 1.5 hours to 3 hours after sunset). The phototactic rate curves of insect orders differed among different spectral LEDs. We proposed a method to predict the relative attractiveness of LEDs to insects and orders by calculating the relative attraction coefficient ( ) of each narrow-spectrum LED and assigning as a coefficient to the spectral irradiance percentage of the corresponding band of the LEDs to be predicted. The model-calculated relative attraction was highly significantly correlated with both the experimentally obtained attraction and the spectral response of insect vision. The results demonstrate that the attractiveness of broad-spectrum LEDs to insects can be altered, evaluated, and predicted through narrow-spectrum LEDs. Our findings will aid the development of ecological light sources, ecological conservation, and improvements in urban light ecology.